Interaction between Underlying Diseases and Income Sufficiency Affecting Elderly Care as a Role of Local Government Organization and the Elderly s’ Care Need from Local Government Organization According to Opinion of the Home-Bound Elderly, Trang Province - Singweratham, Noppcha; Nawsuwan, Kittiporn; Singhasame, Prapaipis; Kramutkant, Rungaroon; Jaisomkom, Anyapaksorn (Princess of Naradhiwas University Journal, 2020)
This descriptive research aimed to determine the elderly care as a role of local government organization and the elderlys’ care needs from local government organization as well as interaction between underlying diseases and income sufficiency affecting elderly care as a role of local government organization and the elderlys’ care needs from local government organization according to opinion of the home-bound elderly. Sample were 727 home-bound elderly in Trang province using multi-stage random sampling. Instrument was questionnaire which alpha cronbach coefficient of .97 and .89. Data were analyzed using frequency, percentage and two-way MANOVA. Results revealed that the overall score for the elderly care as a role of local government organization was moderate level (= 1.90, S.D.=0.79) and the overall score for the elderlys’ care needs from local government organization according to opinion of the home-bound elderly in Trang province was high level (= 2.28, S.D.=0.63). There was a statistically significant interaction between underlying diseases and income sufficiency affecting elderly care as a role of local government organization and the elderlys’ care needs from local government organization according to opinion of the home-bound elderly in Trang province (p=.05 and p=.001, respectively). A local government organization should encourage the elderly to save money and prepare themselves before entering elderhood as well as health literacy, especially in terms of health risk reduction and medical expenditure.